Development of nutrition education website media to prevent anemia in adolescent girls - Umi Mahmudah; Mulus Gumilar; Agus Sulaeman; Lintang Purwara Dewanti (Poltekkes Kemenkes Bandung, 2026)
Background: Adolescent girls are vulnerable to iron-deficiency anemia due to increased iron requirements during growth and menstruation, inadequate dietary intake, and unhealthy eating habits. According to the 2018 Indonesian Basic Health Research (Riskesdas), the prevalence of anemia among females aged 15–24 years was 32.0% nationally and 41.5% in West Java. Nutrition education through digital media has the potential to support anemia prevention among adolescents. Objective: This study aimed to develop a website-based nutrition education medium for anemia prevention among adolescent girls and to evaluate its feasibility. Methods: This research and development study employed the ADDIE model. The analysis stage involved a Focus Group Discussion with 10 adolescent girls to identify educational needs and media preferences. The design stage developed the website structure and educational content, followed by website production in the development stage. Implementation included validation by two media experts, two nutrition experts, and a small-group trial involving 27 adolescent girls. Evaluation consisted of revising the website based on expert and user feedback. Feasibility was assessed using a five-point Likert-scale questionnaire. Results: The website achieved average feasibility scores of 86.42% from media experts and 83.64% from content experts, indicating that it was highly feasible. The small-group trial yielded scores above 89% across all evaluation domains, indicating high user acceptance. Conclusion: The developed website-based nutrition education medium was considered highly feasible and well accepted by adolescent girls, indicating its potential as an educational tool for anemia prevention.